2009
DOI: 10.4314/jasem.v11i1.46832
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements Profile among Alcohol Abusers in a Nigerian Community

Abstract: Alcohol abuse has been associated with Trace elements deficiencies which have been known to cause Neuro Psychiatric Disorders. The focus of this study being on locally brewed alcohol is to establish the pattern if any of trace elements derangements. The trace element profile among alcohol abusers in a Nigerian Community was analysed using the 4 -item CAGE instrument to separate alcohol abusers, social drinkers, and total abstainers. The Royal College of Physicians' criteria 1987 for Alcohol abuse was also used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The drinking of alcohol was not statistically associated with blood Cu concentration. Some literature studies did not find differences between drinkers and abstainers [37], others noted a relationship between Cu blood levels and consumption of wine [38]. This metal has been found in wine as a residue of the Cu-based pesticide treatment of grapes and the migration from containers [39].…”
Section: Discussionmentioning
confidence: 99%
“…The drinking of alcohol was not statistically associated with blood Cu concentration. Some literature studies did not find differences between drinkers and abstainers [37], others noted a relationship between Cu blood levels and consumption of wine [38]. This metal has been found in wine as a residue of the Cu-based pesticide treatment of grapes and the migration from containers [39].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has implied the influence of these exposures onto the concentration of trace elements. Different levels of physical activity (68) weight category (38,69), smoking status (70), alcohol consumption (71) and diet (72,73) were reported to also influence the concentrations. Therefore, there is a need to look more specifically into environmental exposures, which are likely to disclose changes in the level of the elements.…”
Section: Future Direction Of Trace Elements Study and Crcmentioning
confidence: 99%
“…Previous research has shown that ADS patients are predisposed to Zinc (hypozincemia) and magnesium (hypomagnesemia) deficiencies [ 16 - 21 ]. This was attributed to various reasons that include alcohol-induced diuresis (excessive urination) and liver failure resulting in abnormal absorption and transport, among others [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%